Effect of face masks on speech perception in noise of individuals with hearing aids - Choi, Jung Ho; Choi, Hyo Jung; Kim, Dong Hyun; Park, Ji Hye; An, Yong-Hwi; Shim, Hyun Joon (Frontiers in Neuroscience, 2022)
Although several previous studies have confirmed that listeners find it difficult to perceive the speech of face-mask-wearing speakers, there has been little research into how masks affect hearing-impaired individuals using hearing aids. Therefore, the aim of this study was to compare the effects of masks on the speech perception in noise of hearing-impaired individuals and normal-hearing individuals. We also investigated the effect of masks on the gain conferred by hearing aids. The hearing-impaired group included 24 listeners (age: M = 69.5, SD = 8.6; M:F = 13:11) who had used hearing aids in everyday life for > 1 month (M = 20.7, SD = 24.0) and the normal-hearing group included 26 listeners (age: M = 57.9, SD = 11.1; M:F = 13:13). Speech perception in noise was measured under no mask–auditory-only (no-mask–AO), no mask–auditory–visual (no-mask–AV), and mask–AV conditions at five signal-to-noise ratios (SNRs; −16, −12, −8, −4, 0 dB) using five lists of 25 monosyllabic Korean words. Video clips that included a female speaker’s face and sound or the sound only were presented through a monitor and a loudspeaker located 1 m in front of the listener in a sound-attenuating booth. The degree of deterioration in speech perception caused by the mask (no-mask–AV minus mask–AV) was significantly greater for hearing-impaired versus normal-hearing participants only at 0 dB SNR (Bonferroni corrected p < 0.01). When the effects of a mask on speech perception, with and without hearing aids, were compared in the hearing-impaired group, the degree of deterioration in speech perception caused by the mask was significantly reduced by the hearing aids compared with that without hearing aids at 0 and −4 dB SNR (Bonferroni corrected p < 0.01). The improvement conferred by hearing aids (unaided speech perception score minus aided speech perception score) was significantly greater at 0 and −4 dB SNR than at −16 dB SNR in the mask–AV group (Bonferroni corrected p < 0.01). These results demonstrate that hearing aids still improve speech perception when the speaker is masked, and that hearing aids partly offset the effect of a mask at relatively low noise levels.